Analisis Keamanan Jaringan dari Serangan DoS pada Sistem Inventaris Sanggar Tari Natya Lakshita menggunakan IDS - Zahra Arwananing Tyas; Arizona Firdonsyah; Wulan Ramdhani (Faculty of Computer Science, University of Jember, 2022)
Information technology is advancing very quickly. Currently, there is highly qualified support for internet facilities. A quality internet service has both advantages and disadvantages for its users. An example of the negative impact of the development of internet technology is attacks from irresponsible parties or often called hackers. Sanggar Tari Natya Lakshita’s Inventory System is a newly built system, so attack testing is needed because network security is important to maintain data integration in the network. The test is carried out using a DoS attack with the LOIC tool. IDS is the method used in research with the Snort tool that functions as an intruder detector. The study aims to determine the results and effects of attacks on the Inventory System and determine how the IDS framework works with the Snort tool in detecting attacks. carried using 1 computer and 1 laptop. The results of the attack on the inventory system showed that Snort succeeded in detecting an attack sent by LOIC by displaying the attacker's IP and IP target through port 80, then the recommendations were given related to the stages of handling network security based on CSIRT guidelines at Sanggar Tari Natya Lakshita that can be implemented.